Turbulent dipolarization regions in the Earth’s magnetotail: ion fluxes and magnetic field changes - Kozak, Liudmyla; Kronberg, Elena A.; Petrenko, Bohdan; Blöcker, Aljona; Akhmetshyn, Roman; Ballai, Istvan; Fedun, Viktor (Frontiers in Astronomy and Space Sciences, 2023)
In this work, we consider the dynamics of ion fluxes and magnetic field changes in turbulent regions of magnetotail dipolarizations. The data from the Cluster-II mission (magnetic field measurements from fluxgate magnetometers (FGM) and energetic charged particle observations from RAPID spectrometers) were used for the analysis. We study individual events and investigate statistically the changes of charged particle fluxes during magnetic field dipolarizations observed during 2001-2015. Received changes in the spectral index indicate that CNO+ ions undergo stronger acceleration during dipolarization than protons and helium ions. Before dipolarization front monotonic growth the ions flux is observed (the maximum of flux is observed at 1-1,5 min after the start of dipolarization) in the range of ∼ 92 -374 keV for proton; in the energy range ∼ 138 -235 keV for He+ and in the energy range of 414 -638 keV for CNO+ ions. Flux increase before arriving dipolarization front may result from the reflection of plasma sheet ions at the dipolarization front and the result of the resonant interactions of ions with low-frequency electromagnetic waves.